A synergy-column envelope meshing pair profile for single screw compressors. (February 2019) - Liu, Feilong; Feng, Junhao; Xie, Jia; Feng, Quanke; Van Den Broek, Martijn; De Paepe, Michel
Multi-column envelope engaging couples have been proposed for single screw compressors to reduce the friction and prolong the operational life. However, little is mentioned about the relationship between columns at opposite sides of the star-wheel teeth. An imbalance in the lubricant film forces would appear and influence the lubrication between the tooth and the groove. During a real design process, it is necessary to try several times for each different type of compressor to find the optimal combination of columns. In part, due to the large number of columns, it also makes both manufacturing processing and product testing difficult. In this paper, a synergy-column design method and its related manufacturing methods are presented. The locations and relationships of the designed columns can be prescribed by given the tooth width. Manufacturing of the rotor and star-wheel shows the new design method can be more efficient through processing. The stable operation results prove that the synergy-column envelope meshing pair can solve the star-wheel's wear-out problem.